FIST organised Biotechnology Seminar - Nazira, Mahmud
A biotechnology seminar was jointly held by Pahang Government and Universiti Malaysia Pahang (UMP)’s Faculty of Industrial Sciences & Technology Faculty (FIST) on March 3, 2012.